(untitled) (ҚазҰУ хабаршысы. Экономика сериясы, 2017)
The study of cross-national policy convergence is at the centre of political science research. This trend is linked to an increased interest in globalization and in the domestic impact of European integration. The paper provides a comparative study of responses of the United Kingdom and France to the common stimulus of structural changes in the telecommunication industry. During the 1980- 1998s these two countries implemented liberalisation and privatisation policies. It will examine how the similarities in outcomes and differences in the process can be explained. The paper will try to find answers for the following question: how do global forces direct policy convergence? To what extent do countries respond for these forces? Does the strong growth of economic and institutional interrelationship between countries lead to increasingly similar policies across countries? What explains the implementation of similar policies across countries? Under which circumstances can we expect that domestic policies converge or diverge?